A new species of Biophytum (Oxalidaceae) from the Western Ghats (Kerala, India) - Daniel, Jisha; Santhosh Kumar, Ettickal Sukumaran; Decruse, Sabarimuthan William; Rajendraprasad, Madhavan (Phytotaxa, 2020)
A new branched species of Biophytum from the Agasthyamala Biosphere Reserve (Kerala region, SW-India), named B. agasthyamalayanum, is described and illustrated. It is morphologically similar to B. intermedium and B. nudum, but clearly distinct from both these two species especially by the dwarf and slender habit, the smaller leaves, and the obliquely obovate terminal leaflets.